Principles of microeconomics - Gottheil, Fred M. (Cincinnati, Ohio : South-Western College, 1999)
The basics of economic analysis. Introduction to microeconomics. The microeconomics of product markets. The microeconomics of factor markets. The world economy.
Keywords: Microeconomics; Microeconomics